Faktor-Faktor yang Mempengaruhi Kehamilan Remaja Di Indonesia Tahun 2020-2025: Tinjauan Literatur - Eka Mustika, Afrisa; Andriyanti, Andriyanti; Djuari, Lilik (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Adolescent pregnancy is a public health issue that requires special attention due to its serious impact on both maternal and neonatal health. Girls who become pregnant during adolescence are at higher risk of experiencing various complications during pregnancy, childbirth, the postpartum period, and for their newborns. This study aims to identify the factors influencing adolescent pregnancy in Indonesia. The method used is a literature review by searching sources through Google Scholar, ResearchGate, and DOAJ. Data sources were obtained from relevant research articles published between 2020 and 2025. The findings indicate that adolescent pregnancy is influenced by both internal and external factors, including education level, reproductive health knowledge, risky dating behavior, parental roles, peer influence, family economic conditions, and exposure to information media. Understanding these factors can serve as a basis for designing strategies to prevent adolescent pregnancy. The results of this study provide practical contributions as a reference for developing intervention programs for adolescent pregnancy prevention involving families, schools, communities, and healthcare providers.